Deltamethrin increases the fat accumulation in 3T3-L1 adipocytes and Caenorhabditis elegans. (March 2017) - Shen, Peiyi; Hsieh, Tsung-Hsiu; Yue, Yiren; Sun, Quancai; Clark, John M.; Park, Yeonhwa
Abstract: Research has shown that permethrin, a Type-I pyrethroid, increases triglyceride (fat) accumulation in adipocytes. Little is known, however, about any similar effect of deltamethrin, a Type-II pyrethroid, which produces a distinct syndrome of poisoning in mammals compared with permethrin. This study was therefore aimed to explore the role of deltamethrin on fat accumulation in 3T3-L1 adipocytes and Caenorhabditis elegans . Deltamethrin (10 μM) significantly increased the fat accumulation in 3T3-L1 adipocytes and wild type C. elegans compared to respective controls. Deltamethrin decreased the ratio of phosphorylated AMP-activated kinase (pAMPKα) over AMPKα and phosphorylated acetyl-CoA carboxylase (ACC) over ACC, while it increased expression of CCAAT/enhancer-binding protein (C/EBPα) and peroxisome proliferator-activated receptor-γ (PPARγ) in 3T3-L1 adipocytes. Similarly, deltamethrin potentiated fat accumulation in C. elegans without affecting growth or pharyngeal pumping rate. Moreover, deltamethrin significantly reduced the total progeny number and locomotive activities in C. elegans in a dose-dependent manner. Deltamethrin increased fat accumulation via aak-2 (an ortholog of AMPKα) and nhr-49 (a homolog of peroxisome proliferator-activated receptor-α and also downstream target of aak-2 ) mediated mechanisms. The current work is the first report of the effects of deltamethrin on increased fat storage by 3T3- L1 adipocytes and C. elegans via aak-2 (AMPKα ortholog)-mediated mechanism. Highlights: Deltamethrin increased fat accumulation in 3T3-L1 adipocytes. Deltamethrin decreased pAMPKα/AMPKα in 3T3-L1 adipocytes. Deltamethrin increased fat accumulation in C. elegans via aak-2 and nhr-49.